Breed-related number and size of muscle fibres and their response to carcass quality in chickens - Nunyarat Koomkrong (2018)
© N. Koomkrong et al., 2015. The present study was aimed to investigate the number and size of muscle fibre and their relation to carcass quality traits in chickens (slow- and fast-growing chicken strains). A total of 40 one-day-old Arbor Acres broiler (fast-growing) and 40 Thai native chickens (slow-growing) were reared to 45 and 112 days, respectively. The Arbor Acres broilers had heavier live weight, higher breast and thigh percentage than Thai native chickens (P < 0.001). In breast muscle, there was no significant difference in total number of fibres and perimysium thickness. Thai native chickens had smaller fibre diameter and fibre area (P < 0.01), and thicker endomysium in comparison with Arbor Acres broiler (P < 0.001). The difference between the thigh and breast muscle fibre characteristics was not significant (P > 0.05). The fibre diameter was positively correlated with live weight (P < 0.05) and breast percentage (P < 0.01). Endomysium thickness was correlated with live weight and breast percentage (P < 0.05). There was no significant difference for the correlation between muscle fibre characteristics and thigh muscle. These results suggest that muscle fibre characteristics might be related to carcass quality.